1994
DOI: 10.1111/j.1600-0609.1994.tb00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of younger versus older B‐cell chronic lymphocytic leukemia patients for clinical presentation and prognosis. A retrospective study of 53 cases

Abstract: Fifty‐three patients affected with B‐cell chronic lymphocytic leukemia (CLL) younger than 50 years and observed in two hematological institutions have been retrospectively evaluated in order to verify whether this disease has different clinico‐hematological features at presentation and different prognosis as compared to older cases. In our experience young cases with B‐CLL diagnosis, confirmed by immunophenotype in 90.5% of patients, accounted for 7.1% of the whole CLL population. Sex distribution, mean periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
(18 reference statements)
1
14
0
1
Order By: Relevance
“…long lymphocyte doubling time, bone marrow patterns, smoldering CLL 19 ) were able to identify young patients with a longer overall survival. [7][8][9] The present analysis showed that the same biological parameters reported to have an impact on outcome in non-selected CLL cohorts of patients (i.e. ZAP-70 and CD38 expression, IGHV mutational status and FISH cytogenetic abnormalities) applied to patients ≤55 years, and that these factors retained their independent impact in this subgroup of patients individually stratified according to age, gender and Rai stage.…”
mentioning
confidence: 72%
“…long lymphocyte doubling time, bone marrow patterns, smoldering CLL 19 ) were able to identify young patients with a longer overall survival. [7][8][9] The present analysis showed that the same biological parameters reported to have an impact on outcome in non-selected CLL cohorts of patients (i.e. ZAP-70 and CD38 expression, IGHV mutational status and FISH cytogenetic abnormalities) applied to patients ≤55 years, and that these factors retained their independent impact in this subgroup of patients individually stratified according to age, gender and Rai stage.…”
mentioning
confidence: 72%
“…[22][23][24][25] Due to these profound changes, data from historical reports on clinical outcomes of younger patients with CLL are of uncertain relevance in the modern era. 6,[8][9][10][11] In the present study, we aim to describe the clinical characteristics, time to first treatment and overall survival of CLL patients ≤55 years old in the current era.…”
Section: Introductionmentioning
confidence: 99%
“…<200 patients) and are more than two decades old. 6,[8][9][10][11] The most recent and largest series was reported in 1999 and included 204 patients. 7 The past decade has been a time of tremendous change in the clinical care of patients with CLL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations